Effect of Series Circuit on the Lactose Bioelectricity of a Microbial Fuel Cell System using Lactobacillus bulgaricus - Hayati, Dini Noor; Nuryanto, Rahmad; Suyati, Linda (JURNAL SAINS DAN MATEMATIKA, 2015)
The need for alternative energy, especially electricity at this time is increasing. The decreasing amount of fuel that cannot be updated, encouraging scientists to conduct researches in finding alternative energy sources which are environmentally friendly, one of the alternative energy is the Microbial Fuel Cell (MFC). The research on the effects of a series circuit on the production of lactose bioelectricity microbial fuel cell system using Lactobacillus bulgaricus has been conducted. This study aim was to assess the effect on the production series circuit lactose bioelectricity MFC system using microbes Lactobacillus bulgaricus. Stages of research included a microorganism preparation of Lactobacillus bulgaricus, and measuring the potential difference in a single, series 1 and series 2 circuits in the MFC system. The potential difference on the measurement of a single, series 1 and series 2 on the substrate lactose were 45 mV / 100mL; 57 mV / 100mL; 58 mV / 100mL respectively where the power were 105.75x10-6 mW; 136x10-6 mW; 139.2x10-6 mW. These results suggested that series circuit was able to increase the potential difference and power on the substrate lactose and tofu whey the MFC system according to Ohm’s law. Keywords: Lactose, microbial fuel cell, Lactobacillus bulgaricus, a series circuit